2005
DOI: 10.1016/j.cub.2005.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Building Complexity: An In Vitro Study of Cytoplasmic Dynein with In Vivo Implications

Abstract: Multiple dyneins working together suppress shortcomings of a single motor and generate robust motion under in vitro conditions. There appears to be no need for additional cofactors (e.g., dynactin) for this improvement. Because cargos are often driven by multiple dyneins in vivo, our results show that changing the number of dynein motors could allow modulation of dynein function from the mediocre single-dynein limit to robust in vivo-like dynein-driven motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
209
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(255 citation statements)
references
References 37 publications
42
209
2
2
Order By: Relevance
“…It has previously been shown that multiple individual mammalian dynein motors can transport artificial cargoes over long distances in vitro (Mallik et al , 2005) and that multiple dyneins are associated with membrane‐bound cargoes inside cells (Welte et al , 1998; Hendricks et al , 2012; Rai et al , 2013). Given the involvement of multiple dyneins, an important question is how activation of processivity of individual motors by dynactin contributes to cargo transport in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that multiple individual mammalian dynein motors can transport artificial cargoes over long distances in vitro (Mallik et al , 2005) and that multiple dyneins are associated with membrane‐bound cargoes inside cells (Welte et al , 1998; Hendricks et al , 2012; Rai et al , 2013). Given the involvement of multiple dyneins, an important question is how activation of processivity of individual motors by dynactin contributes to cargo transport in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The motile behaviour of mammalian dynein has been studied using complexes purified from brain (Mallik et al , 2005; Ross et al , 2006; Miura et al , 2010; Ori‐McKenney et al , 2010; Walter et al , 2010) and tissue culture cells (Ichikawa et al , 2011), as well as complexes reconstituted from individual, recombinant components (Trokter et al , 2012). Movement of individual mammalian dynein complexes has been assayed by adhering the motor to beads (King & Schroer, 2000; Mallik et al , 2005; Walter et al , 2010), labelling accessory proteins (Ross et al , 2006; Miura et al , 2010) or by GFP tagging of the motor (Trokter et al , 2012). The extent to which individual dynein complexes can take multiple successive steps without detaching from the microtubule, a behaviour termed processivity, varied in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). We developed a program that parses the time series of droplet positions into a sequence of runs and pauses [14,24].…”
Section: Methodsmentioning
confidence: 99%
“…Typically, travel in a given direction (a "run") is short (1-2 μm) [1] though longer runs (~10 μm) are observed in some systems [10,12,13]. This observation is surprising since in vitro work suggests that when cargos are moved by multiple motors, they have very long run lengths [6,14,15]. In vivo, net transport of bi-directional cargos is ultimately controlled by the direction-switching rate [16,17], which is used to control how much time a cargo spends moving toward the plus versus minus-end of the microtubules.…”
Section: Introductionmentioning
confidence: 99%